Lack of reversal of oxidative damage in renal tissues of lead Acetate-treated rats (2014)
Removal of lead from the environment of man or otherwise, the movement of man from lead-contaminated areas has been employed as a means of abatement of the toxic effects of lead. Whether toxic effects in already-exposed individuals subside after lead withdrawal remains unanswered. To understand the reversibility of nephrotoxicity induced by lead acetate, male Wistar rats were orally exposed to 0.25, 0.5, and 1.0 mg/mL of lead acetate for 6 weeks. Activities of glutathione-s-transferase, catalase (CAT), superoxide dismutase (SOD) and the concentrations of hydrogen peroxide (H2O2), and malondialdehyde increased significantly (p<0.05) in a dosedependent manner, whereas reduced glutathione (GSH) level and glutathione peroxidase activity were significantly reduced. The pattern of alterations in most of the oxidative stress and antioxidant parameters remained similar in rats from the withdrawal period, although CAT and SOD activities reduced, in contrast to their elevation during the exposure period. Serum creatinine levels were significantly elevated in both exposure and withdrawal experiments whereas serum blood urea nitrogen levels were not significantly different from the control in both exposure and withdrawal periods. The histological damage observed include multifocal areas of inflammation, disseminated tubular necrosis, and fatty infiltration of the kidney tubules both at exposure and withdrawal periods. The results suggest that lead acetate-induced nephrotoxicity by induction of oxidative stress and disruption of antioxidant. The aforementioned alterations were not reversed in the rats left to recover within the time course of study.